Orphan nuclear receptor TLX regulates astrogenesis by modulating BMP signaling - Qin, Song; Niu, Wenze; Iqbal, Nida; Smith, Derek K.; Zhang, Chun-Li (Frontiers in Neuroscience, 2014)
Neural stem cells (NSCs) are self-renewing multipotent progenitors that generate both neurons and glia. The precise control of NSC behavior is fundamental to the architecture and function of the central nervous system. We previously demonstrated that the orphan nuclear receptor TLX is required for postnatal NSC activation and neurogenesis in the neurogenic niche. Here, we show that TLX modulates BMP-SMAD signaling to control the timing of postnatal astrogenesis. Genes involved in the BMP signaling pathway, such as Bmp4, Hes1, and Id3, are upregulated in postnatal brains lacking Tlx. Chromatin immunoprecipitation and electrophoretic mobility shift assays reveal that TLX can directly bind the enhancer region of Bmp4. In accordance with elevated BMP signaling, the downstream effectors SMAD1/5/8 are activated by phosphorylation in Tlx mutant mice. Consequently, Tlx mutant brains exhibit an early appearance and increased number of astrocytes with marker expression of glial fibrillary acidic protein (GFAP) and S100B. Taken together, these results suggest that TLX tightly controls postnatal astrogenesis through the modulation of BMP-SMAD signaling pathway activity.